Solder alloy, solder paste, solder ball, solder preform and solder joint

A solder alloy with a unique composition and As-enriched layer addresses the challenges of balancing temperature cycling, drop impact resistance, and surface yellowing in small electronic devices, while maintaining wettability and preventing solder paste thickening.

JP2025061124APending Publication Date: 2025-04-10SENJU METAL IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025003030
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-05-27
Filing Date
2025-01-08
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing solder alloys struggle to balance excellent temperature cycling characteristics with drop impact resistance, while also suppressing yellow changes on the surface and maintaining wettability, especially in small electronic devices like mobile phones and mobile computers.

Method used

A solder alloy composition with specific mass percentages of Ag (0.2-1.2%), Cu (0.6-0.9%), Bi (1.2-3.0%), In (0.01-2.0%), Sb (0.02-1.0%), and As (0.0040-0.025%), where an As-enriched layer is formed on the surface, enhancing drop impact resistance, temperature cycling characteristics, and suppressing yellow changes and viscosity increase in solder paste.

Benefits of technology

The solder alloy achieves excellent temperature cycling characteristics and drop impact resistance, suppresses yellow changes on the surface, maintains high wettability, and inhibits the thickening of solder paste over time, making it suitable for small electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061124000001_ABST
    Figure 2025061124000001_ABST
Patent Text Reader

Abstract

To provide a solder alloy which exhibits excellent temperature cycle characteristics and drop impact resistance, suppresses yellowing, maintains excellent wettability and can suppress an increase over time in the viscosity of a solder paste; and a solder paste, a solder ball, a solder preform and a solder joint that are obtained using this solder alloy.SOLUTION: This solder alloy contains, in terms of mass%, 0.2-1.2% of Ag, 0.6-0.9% of Cu, 1.2-3.0% of Bi, 0.01-2.0% of In, 0.02-1.0% of Sb and 0.0040-0.025% of As, with the remainder consisting of Sn.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solder alloy, a solder paste, a solder ball, a solder preform, and a solder joint. [Background technology]

[0002] Methods for soldering electronic components include the iron method, the flow method, the reflow method, and the like. The reflow method involves applying a solder paste consisting of solder powder and flux to the required locations on a board, mounting electronic components on the applied areas, and then melting the solder paste in a reflow furnace to solder the electronic components to the board. This reflow method not only allows soldering at multiple locations in one operation, but also provides excellent productivity and reliability, as no bridging occurs even when soldering electronic components with narrow pitches, and no solder adheres to unnecessary locations.

[0003] Incidentally, as disclosed in Japanese Patent Laid-Open Publication No. 5-050286, a solder alloy that has been widely used in the past is a Sn-Ag-Cu solder alloy with an Ag content of 3-5 mass% and a Cu content of 0.5-3 mass%. This solder alloy has excellent temperature cycle characteristics and creep characteristics. In particular, the temperature cycle characteristics are an important factor in evaluating the life of electronic devices and in providing product guarantees.

[0004] However, because Sn-Ag-Cu solder alloys are relatively hard, when they are used in small devices such as mobile phones, they are prone to cracking at the interface between the part and the soldered part due to being dropped, which is known as "interfacial peeling." This interfacial peeling is unlikely to occur in boards that use flow soldering, which has a relatively large amount of solder alloy in the joints, but it is likely to occur in boards that use a small amount of solder alloy in the joints and have fine joints soldered by reflow soldering.

[0005] For circuit boards that are soldered by reflow soldering, solder paste, solder balls, solder preforms, etc. are used. For repairing solder joints, oil-containing solder is used. Printed circuit boards that use the above-mentioned solder alloys are particularly prone to problems with interface peeling. Therefore, solder alloys with excellent temperature cycle characteristics and drop impact resistance are being studied.

[0006] Patent Document 1 discloses a solder alloy that is resistant to drop impact and is used for soldering Cu lands, and contains 0.8 to 2.0 mass % Ag, 0.05 to 0.3 mass % Cu, and In, Ni, Pt, Sb, Bi, Fe, Al, and P.

[0007] Patent Document 2 discloses a Sn-Ag-Cu-Bi solder alloy containing a solid solution element as a solder alloy with excellent temperature cycle characteristics. This solder alloy has an alloy structure consisting of a supersaturated solid solution or a solid solution in which the solid solution element is precipitated at room temperature, and at high temperatures in a heat cycle environment, has an alloy structure consisting of a solid solution in which the solid solution element precipitated at low temperatures is re-dissolved in the Sn matrix.

[0008] Patent Document 3 discloses a solder alloy containing Bi and Sb in a Sn-Ag-Cu solder composition. In this solder alloy, Bi and Sb form a solid solution with Sn, and Ag and Cu form an intermetallic compound with Sn, and the mechanical strength is maintained by the microstructure of the solid solution and intermetallic compound.

[0009] In addition, because the main component of the above-mentioned solder alloy is Sn, when the surface of the solder alloy oxidizes, it forms an oxide film of SnO, which turns yellow. The thicker the SnO film, the more yellow the solder surface becomes. If the surface of the solder alloy turns yellow and loses its metallic luster, the solder alloy may not be detected during automatic processing of image recognition of the solder alloy, and the solder alloy may not be recognized even if it is actually present.

[0010] As an example of a conventional solder material that suppresses yellowing of the surface, Patent Document 4 describes a solder layer made of a metal material made of an alloy with an Sn content of 40% by mass or more or a metal material with an Sn content of 100% by mass, and a coating layer that covers the surface of the solder layer, the coating layer being a sphere with a diameter of 1 to 1000 μm, the coating layer being a SnO film formed on the outside of the solder layer, and a SnO 2 The solder material is disclosed in which a film is formed and the thickness of the coating layer is greater than 0 nm and less than 4.5 nm. The solder material is made of SnO 2 The formation of the film suppresses yellowing of the solder material surface. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] WO2006 / 129713A1 [Patent Document 2] WO2009 / 011341A1 [Patent Document 3] Japanese Patent Application Publication No. 9-327790 [Patent Document 4] Patent No. 5807733 Summary of the Invention [Problem to be solved by the invention]

[0012] The solder alloys described in Patent Documents 2 and 3 do not take into consideration drop impact resistance. It is difficult to say that the drop impact resistance of solder joints with small soldering areas is particularly excellent. As electronic devices have become more powerful and compact in recent years, the electronic components incorporated therein have also become smaller and more functional. Although the number of electrodes in electronic devices has increased in recent years, the overall size of the devices has become smaller.

[0013] Thus, the solder joints that join the electrodes of small electronic components are becoming smaller, but if the solder alloy that makes up the solder joint is weak in resistance to drop impact, the solder joint can easily peel off when the electronic device receives an impact such as being dropped. Small, densely packed products such as mobile phones and mobile computers can only be soldered by reflow soldering using solder paste or solder balls. This means that the amount of solder joints used is becoming very small, further deteriorating the drop impact resistance of the solder joints.

[0014] Next, the temperature cycle characteristics of electronic devices are an important factor related to the lifespan of the electronic devices. Mobile phones and mobile computers are not always used in air-conditioned rooms, but are often used in high-temperature environments such as inside a car or low-temperature environments such as outdoors on a snowy day. For this reason, excellent temperature cycle characteristics are an essential condition, and solder alloys used in mobile devices must have excellent temperature cycle characteristics.

[0015] That is, because the thermal expansion coefficients of the electronic components and the board that make up an electronic device are significantly different, depending on the environment in which the electronic device is used, stress is applied to the solder joints, which can cause cracks in the solder joints. If the number of temperature cycles increases, the solder joints will break. This is generally called thermal fatigue. Solder alloys used in mobile phones and mobile computers are required to be resistant to thermal fatigue and have good temperature cycle characteristics.

[0016] However, it cannot be said that a solder alloy with excellent drop impact resistance also has excellent temperature cycle characteristics. For example, the conventional solder alloy described in Patent Document 1, which takes drop impact resistance into consideration, has a reduced Ag and Cu content in the Sn-Ag-Cu solder alloy. This reduces Cu generated at the interface between the electrode and the solder alloy. 6 Sn 5 Or Ag 3By preventing the thickness of intermetallic compounds such as Sn from increasing, peeling from the interface between the electrode and the solder alloy is prevented, ensuring drop impact resistance. On the other hand, reducing the amount of Ag or Cu from a conventional Sn-Ag-Cu solder alloy results in a deterioration of the temperature cycle characteristics, which is an advantage of Sn-Ag-Cu solder alloys. Thus, until now, no solder alloys have been developed that have both temperature cycle characteristics and drop impact resistance.

[0017] Furthermore, in addition to drop impact resistance and temperature cycle characteristics, the effect of suppressing yellowing on the solder alloy surface is an important factor in automatic processing of image recognition of solder alloys. 2 To form the film, high-energy plasma irradiation is required, which makes the manufacturing process complicated. In addition, elements such as P, Ge, and Ga have been added to solder alloys whose main component is Sn in order to suppress the yellowing of the surface. These elements have a smaller free energy of oxide formation than Sn, and are very easily oxidized. Therefore, when forming a solder ball from molten solder, elements such as P, Ge, and Ga are oxidized and concentrated on the surface instead of Sn, which suppresses the yellowing of the solder surface.

[0018] However, while wettability is generally required for solder alloys, increasing the content of these elements and increasing the degree of concentration in order to suppress the yellowing of the solder alloy surface results in a decrease in the wettability of the solder alloy.

[0019] In addition, in joining and assembling electronic components to a substrate of an electronic device, soldering using solder paste is advantageous in terms of cost and reliability. The application of the solder paste to the substrate is performed, for example, by screen printing using a metal mask. In order to ensure the printability of the solder paste, the viscosity of the solder paste needs to be appropriate.

[0020] When a solder powder with suppressed yellowing is used, the amount of activator used in the solder paste can be increased or a highly active one can be used to compensate for the deterioration of wettability. However, when an activator or the like is used to improve wettability, the viscosity of the solder paste increases over time. For this reason, conventional solder alloys could not simultaneously satisfy the drop impact resistance, temperature cycle properties, and yellowing suppression effect, as well as the viscosity increase suppression effect when used in a solder paste, and further investigation was necessary.

[0021] The problem to be solved by the present invention is to provide a solder alloy that has excellent temperature cycle characteristics and drop impact resistance, is inhibited from yellowing, maintains excellent wettability, and can inhibit an increase in the viscosity of the solder paste over time, and to provide a solder paste, a solder ball, a solder preform, and a solder joint that use this solder alloy. [Means for solving the problem]

[0022] The inventors of the present invention have found that in a Sn-Ag-Cu based solder alloy composition, if the Cu content deviates from near the eutectic, the temperature cycle characteristics are reduced, that even if the Ag content deviates from near the eutectic, the temperature cycle characteristics are less degraded than with Cu, that the temperature cycle characteristics are improved by adding In to Bi and Sb in place of reducing the Ag content, that the inclusion of a certain amount of As suppresses yellowing and maintains excellent wettability, and that when used in a solder paste, it exerts a thickening suppression effect, and have completed the present invention. The details are as follows.

[0023] When a solder joint is exposed to a temperature cycle, the structure of the solder alloy becomes coarse, so that a solder alloy with a fine structure generally has excellent temperature cycle properties. Considering that the solder alloy described in Patent Document 3 has an Ag content of 3.0 mass % or 3.4 mass % in the solder alloy used in the examples, Patent Document 3 discloses a technology of a solder alloy with an Ag content close to eutectic. In contrast, in the present invention, the Ag content is set to 0.2 to 1.2 mass % in order to improve drop impact resistance. However, it has been found that the temperature cycle properties of the solder alloy described in Patent Document 3 cannot be said to be good just by reducing the Ag content.

[0024] Therefore, in the present invention, in addition to adding Bi and Sb to the Sn-Ag-Cu solder alloy composition as in the solder alloy described in Patent Document 3, In was further added. As a result, even when the Ag content was reduced to 0.2 to 1.2 mass%, a solder alloy was obtained which not only had low thermal fatigue like the conventional Sn-Ag-Cu-Bi-Sb solder alloy, but also unexpectedly had good temperature cycle characteristics.

[0025] The In contained in the solder alloy according to the present invention is a metal that forms a solid solution with Sn, just like Bi and Sb. Since In has a smaller atomic weight than Bi and Sb that form a solid solution with Sn, it is possible for In to enter between Bi and Sb and form a solid-solution strengthened solder alloy with better temperature cycle characteristics.

[0026] Preferably, the content of Bi, which has the largest atomic weight among Bi, Sb, and In, is more than twice as much as In in atomic percent, that is, about four times more by mass percent, so that In fills the gaps between the Bi atoms and the temperature cycle characteristics become even better.More preferably, the content of Bi is three times more than In in atomic percent.

[0027] However, like Zn, In is highly reactive, and when used in solder paste, the viscosity of the solder paste is likely to change over time, making it difficult to handle. In the present invention, it has been discovered that by limiting the In content in the solder alloy, it is possible to use In in solder paste.

[0028] Furthermore, the inventors tried to add a certain amount of As from among various elements to the Sn-Ag-Cu-Bi-In-Sb solder alloy. As mentioned above, in the solder alloy mainly composed of Sn, SnO 2 It is known that As forms a film, and since solder alloys containing As are generally considered to have poor wettability, its addition to solder alloys has been avoided. However, unexpectedly, it was discovered that, in addition to improving the temperature cycle characteristics and drop impact resistance, the formation of an As-enriched layer on the surface of the solder alloy suppresses yellowing and provides an excellent effect of suppressing thickening, thereby maintaining high wettability, and the present invention was completed.

[0029] The present invention, which was obtained based on these findings, is as follows. (1) A solder alloy containing, by mass%, 0.2-1.2% Ag, 0.6-0.9% Cu, 1.2-3.0% Bi, 0.01-2.0% In, 0.02-1.0% Sb, 0.0040-0.025% As, and the remainder being Sn, with an As-enriched layer, the presence of which is confirmed by the following criteria, and the As-enriched layer is a layer extending from the outermost surface of the solder alloy to SiO 2 The area is up to 2×D1 (nm) in terms of the converted depth, and is the SiO 2 A solder alloy having an equivalent thickness of 0.5 to 8.0 nm. (Judgment criteria) An arbitrary area of ​​700μm×300μm is selected from a sample measuring 5.0mm×5.0mm, and XPS analysis is performed in combination with ion sputtering. One area is selected for each sample, and three analyses are performed once for each of the three samples, for a total of three analyses. If S1>S2 in all three analyses, it is determined that an As-enriched layer has formed. Where: S1: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 0 to 2×D1 (nm) S2: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 2×D1~4×D1 (nm) D1: SiO where the detection intensity of O atoms was the highest in the XPS analysis chart 2 The first SiO atom at which the detection intensity of O atoms becomes half the maximum detection intensity (intensity at Do max) at a depth deeper than the conversion depth (Do max (nm)). 2 Conversion depth (nm).

[0030] (2) A solder paste comprising a solder powder made of the solder alloy described in (1) above and a flux.

[0031] (3) A solder ball made of the solder alloy described in (1) above. (4) A solder preform made of the solder alloy described in (1) above.

[0032] (5) A solder joint formed from the solder alloy described in (1) above. [Brief description of the drawings]

[0033] [Figure 1] FIG. 1 is a chart of an XPS analysis of the surface of a solder ball. [Diagram 2] FIG. 2 is a chart of an XPS analysis of the solder ball surface. [Diagram 3] FIG. 3 is a chart of an XPS analysis of the solder ball surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The present invention will be described in more detail below. In this specification, "%" relating to the solder alloy composition is "mass %" unless otherwise specified.

[0035] 1. Solder alloy (1) Ag: 0.2-1.2% Generally, in solder alloys mainly composed of Sn, Ag is effective for temperature cycle resistance, but on the other hand, adding too much Ag reduces drop impact resistance. In the solder alloy according to the present invention, if the Ag content is less than 0.2%, the amount of Sn-Ag intermetallic compounds formed in the solder alloy is small, the effect of refining the solder structure is not achieved, and the effect of improving the temperature cycle characteristics is not achieved. The lower limit of the Ag content is 0.2% or more, and preferably 0.3% or more. On the other hand, if the Ag content exceeds 1.2%, Ag will be present inside the solder. 3 Since a large amount of Sn is produced and a mesh-like structure is formed, the strength of the solder alloy increases and the drop impact resistance deteriorates, so the upper limit of the Ag content is 1.2% or less, and preferably 1.0% or less.

[0036] (2) Cu: 0.6-0.9% In the solder alloy according to the present invention, if the Cu content is less than 0.6%, the amount of Sn-Cu intermetallic compounds formed in the solder alloy is small, the effect of refining the solder structure is not achieved, and the effect of improving the temperature cycle characteristics is not achieved. The lower limit of the Cu content is 0.6% or more, and preferably 0.7% or more. On the other hand, when the Cu content is more than 0.9%, Cu 6 Sn 5 Therefore, the upper limit of the Cu content is set to 0.9% or less, and preferably 0.8% or less.

[0037] (3) Bi: 1.2-3.0% If the Bi content is less than 1.2%, the amount of Bi dissolved in the Sn in the solder alloy is small, and therefore there is no effect on improving the temperature cycle characteristics. The lower limit of the Bi content is 1.2% or more, and preferably 1.5% or more. On the other hand, if the Bi content is more than 3.0%, the hardness of the solder increases rapidly and the ductility is lost, resulting in poor drop impact resistance. Therefore, the upper limit of the Bi content is 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less.

[0038] (4) In: 0.01 to 2.0% In is effective in improving temperature cycle characteristics. However, since In is a metal that oxidizes easily, its solder alloy also oxidizes easily. The oxidation of In causes the solder alloy to yellow, so the In content must be limited. Furthermore, when a solder alloy containing In is powdered and mixed with flux to make solder paste, the In and flux react, causing the viscosity of the solder paste to change easily over time. If the In content is less than 0.01%, the amount of solid solution of Sn and In in the solder alloy is small, and therefore there is no effect in improving the temperature cycle characteristics. The lower limit of the In content is 0.01% or more, and preferably 0.2% or more. On the other hand, if the In content is more than 2.0%, the solder bump surface turns yellow after reflow, and the viscosity of the solder paste changes over time, which is not preferable. The upper limit of the In content is 2.0% or less, and more preferably 0.5% or less.

[0039] (5) Sb: 0.02 to 1.0% If the Sb content is less than 0.02%, the amount of Sb dissolved in Sn in the solder alloy is small, and therefore there is no effect on improving the temperature cycle characteristics. The lower limit of the Sb content is 0.02% or more, preferably 0.025% or more, and more preferably 0.1% or more. On the other hand, if the Sb content is more than 1.0%, an intermetallic compound of AgSb is generated in the solder alloy, which deteriorates the drop impact resistance. In addition, if the Sb content is more than 1.0%, the wettability of the solder alloy is deteriorated. The upper limit of the Sb content is 1.0% or less, preferably 0.5% or less, and more preferably 0.2% or less.

[0040] (6) As: 0.0040-0.025% As forms an As-enriched layer on the surface of the solder alloy, suppressing yellowing. In addition, when the solder alloy according to the present invention is added as a solder powder to a solder paste, it is possible to suppress the thickening of the solder paste. The lower limit of the As content must be 0.0040% or more in order to fully exert the effect of containing As. On the other hand, when As exceeds 0.025%, the wettability may be deteriorated. The upper limit of the As content is 0.025% or less, preferably 0.020% or less, and more preferably 0.010% or less.

[0041] In the present invention, the As-enriched layer formed by containing As refers to a region in which the As concentration is higher than the average As concentration in the solder material (the As content relative to the mass of the entire solder material). Specifically, the As-enriched layer is a region from the outermost surface of the solder alloy to the SiO 2 It is a region up to a converted depth of 2×D1 (nm), and its presence can be confirmed by the criteria described below. The As-enriched layer is preferably present on at least a portion of the surface side of the solder material, and preferably covers the entire surface.

[0042] The reason why the formation of an As-enriched layer by containing As as in the present invention suppresses yellow discoloration, maintains high wettability, and suppresses the increase in viscosity of the solder paste is unclear, but is presumed to be as follows. The increase in viscosity is thought to be caused by the reaction between Sn or Sn oxide and various additives such as activators contained in the solder paste (flux), which results in the formation of salts or the aggregation of the solder material. When an As-enriched layer exists on the surface as in the solder alloy of the present invention, the As-enriched layer is interposed between the solder alloy and the flux, making it difficult for the above-mentioned reactions to occur, and it is presumed that the above-mentioned effects are simultaneously manifested.

[0043] (6-1) Criteria for determining As-enriched layers An arbitrary 700μm×300μm area is selected from a sample measuring 5.0mm×5.0mm (if the solder material is not in plate form, the solder material (solder powder, solder balls, etc.) is spread tightly over an area of ​​5.0mm×5.0mm), and an XPS analysis is performed in conjunction with ion sputtering. One area is selected for each sample, and the analysis is performed three times in total, once for each of the three samples. If S1≧S2 in all three analyses, it is determined that an As-enriched layer has been formed.

[0044] Here, the definitions of S1, S2 and D1 are as follows. S1: In the XPS analysis chart of the above sample, SiO 2 The integral value of the As detection intensity in the region of 0 to 2×D1 (nm) S2: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 2×D1~4×D1 (nm) D1: SiO where the detection intensity of O atoms was the highest in the XPS analysis chart 2 The first SiO atom at which the detection intensity of O atoms becomes half the maximum detection intensity (intensity at Do max) at a depth deeper than the conversion depth (Do max (nm)). 2 Conversion depth (nm).

[0045] Detailed conditions for the criteria for the above-mentioned As-rich layer are as described in the Examples. When the solder alloy according to the present invention has an As-rich layer on the surface, it is possible to suppress the yellowing of the solder alloy and the increase in the viscosity of the solder paste.

[0046] (6-2) Thickness of As-enriched Layer The thickness of the As-enriched layer (SiO 2 When the thickness of the As-enriched layer is within the above range, yellowing is suppressed, and a solder material with excellent wettability can be obtained.

[0047] (6-3) Yellowness In the present invention, the yellowness b* of the solder alloy in the L*a*b* color system is preferably 0 to 10.0, more preferably 3.0 to 5.7, and most preferably 3.0 to 5.0. If the yellowness b* of the solder material in the L*a*b* color system is within the above range, the yellowness is low and the solder has a metallic luster, so that the solder joint can be accurately detected during automatic processing of image recognition of the solder joint.

[0048] In the present invention, the yellowness index b* can be determined from the color values ​​(L*, a*, b*) by measuring the spectral transmittance using a CM-3500d2600d spectrophotometer (manufactured by Konica Minolta) under a D65 light source and a 10-degree visual field in accordance with JIS Z 8722:2009 "Method of measurement of color - Reflected and transmitted object color."

[0049] (7) Remainder: Sn The balance of the solder alloy according to the present invention is Sn. In addition to the above elements, the solder alloy may contain unavoidable impurities. Even if the solder alloy contains unavoidable impurities, the above effects are not affected.

[0050] 2. Solder paste The solder paste according to the present invention contains a flux and a solder powder.

[0051] (1) Flux components The flux used in solder paste is composed of any one of the following, or a combination of two or more of: organic acids, amines, amine hydrohalides, organic halogen compounds, thixotropic agents, rosin, solvents, surfactants, base agents, polymer compounds, silane coupling agents, and colorants.

[0052] Examples of organic acids include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dimer acid, propionic acid, 2,2-bishydroxymethylpropionic acid, tartaric acid, malic acid, glycolic acid, diglycolic acid, thioglycolic acid, dithioglycolic acid, stearic acid, 12-hydroxystearic acid, palmitic acid, and oleic acid.

[0053] Amines include ethylamine, triethylamine, ethylenediamine, triethylenetetramine, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-Cyanoethyl-2-methylimidazole, 1-Cyanoethyl-2-undecylimidazole, 1-Cyanoethyl-2-ethyl-4-methylimidazole, 1-Cyanoethyl-2-phenylimidazole, 1-Cyanoethyl-2-undecylimidazolium trimellitate, 1-Cyanoethyl-2-phenylimidazolium trimellitate, 2,4-Diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s- Triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihi hydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, 2,4-diamino-6-vinyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine isocyanuric acid adduct, 2,4-Diamino-6-methacryloyloxyethyl-s-triazine, epoxy-imidazole adduct, 2-methylbenzimidazole, 2-octylbenzimidazole, 2-pentylbenzimidazole, 2-(1-ethylpentyl)benzimidazole, 2-nonylbenzimidazole, 2-(4-thiazolyl)benzimidazole, benzimidazole, 2-(2′-hydroxy-5′-methylphenyl)benzotriazole, 2-(2′-hydroxy-3′-tert-butyl-5′-methylphenyl)-5-chlorobenzotriazole, 2-(2′-hydroxy-3′,5′-di-tert-amylphenyl)benzotriazole, 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole, 2,2′-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol], 6 -(2-benzotriazolyl)-4-tert-octyl-6'-tert-butyl-4'-methyl-2,2'-methylenebisphenol, 1,2,3-benzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, carboxybenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol, 1-(1',2'-dicarboxyethyl)benzotriazole, 1-(2,3-dicarboxypropyl)benzotriazole, 1-[(2-ethylhexylamino)methyl]benzotriazole, 2,6-bis[(1H-benzotriazol-1-yl)methyl]-4-methylphenol, 5-methylbenzotriazole, 5-phenyltetrazole, etc.,

[0054] Amine hydrohalides are compounds obtained by reacting an amine with a hydrogen halide. Examples of the amine include ethylamine, ethylenediamine, triethylamine, diphenylguanidine, ditolylguanidine, methylimidazole, and 2-ethyl-4-methylimidazole. Examples of the hydrogen halide include chlorine, bromine, and iodine hydrides.

[0055] Examples of the organic halogen compound include trans-2,3-dibromo-2-butene-1,4-diol, triallyl isocyanurate hexabromide, 1-bromo-2-butanol, 1-bromo-2-propanol, 3-bromo-1-propanol, 3-bromo-1,2-propanediol, 1,4-dibromo-2-butanol, 1,3-dibromo-2-propanol, 2,3-dibromo-1-propanol, 2,3-dibromo-1,4-butanediol, and 2,3-dibromo-2-butene-1,4-diol.

[0056] Examples of the thixotropic agent include wax-based thixotropic agents, amide-based thixotropic agents, and sorbitol-based thixotropic agents. Examples of the wax-based thixotropic agents include castor hardened oil. Examples of the amide-based thixotropic agents include monoamide-based thixotropic agents, bisamide-based thixotropic agents, and polyamide-based thixotropic agents, and more specifically, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, saturated fatty acid amide, oleic acid amide, erucic acid amide, unsaturated fatty acid amide, p-toluenemethane amide, aromatic amide, and methylenebisstearic acid amide. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc. Examples of the sorbitol-based thixotropic agents include dibenzylidene-D-sorbitol, bis(4-methylbenzylidene)-D-sorbitol, etc.

[0057] Examples of the base agent include nonionic surfactants, weak cationic surfactants, and rosin.

[0058] Examples of the nonionic surfactant include polyethylene glycol, polyethylene glycol-polypropylene glycol copolymers, aliphatic alcohol polyoxyethylene adducts, aromatic alcohol polyoxyethylene adducts, and polyhydric alcohol polyoxyethylene adducts.

[0059] Examples of the weak cationic surfactant include diamine-terminated polyethylene glycol, diamine-terminated polyethylene glycol-polypropylene glycol copolymer, aliphatic amine polyoxyethylene adducts, aromatic amine polyoxyethylene adducts, and polyvalent amine polyoxyethylene adducts.

[0060] Examples of rosin include raw rosins such as gum rosin, wood rosin, and tall oil rosin, as well as derivatives obtained from the raw rosins. Examples of the derivatives include refined rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin, and α,β-unsaturated carboxylic acid modified products (acrylated rosin, maleic rosin, fumarated rosin, etc.), as well as purified products, hydrogenated products, and disproportionated products of the polymerized rosin, as well as purified products, hydrogenated products, and disproportionated products of the α,β-unsaturated carboxylic acid modified products, and two or more of them can be used. In addition to the rosin-based resin, the composition can further contain at least one resin selected from terpene resins, modified terpene resins, terpene phenolic resins, modified terpene phenolic resins, styrene resins, modified styrene resins, xylene resins, and modified xylene resins. Examples of the modified terpene resins that can be used include aromatic modified terpene resins, hydrogenated terpene resins, and hydrogenated aromatic modified terpene resins. Examples of the modified terpene phenolic resins that can be used include hydrogenated terpene phenolic resins. The modified styrene resin may be a styrene-acrylic resin, a styrene-maleic acid resin, etc. The modified xylene resin may be a phenol-modified xylene resin, an alkylphenol-modified xylene resin, a phenol-modified resol-type xylene resin, a polyol-modified xylene resin, a polyoxyethylene-added xylene resin, etc.

[0061] Examples of the solvent include water, alcohol-based solvents, glycol ether-based solvents, terpineols, etc. Examples of the alcohol-based solvent include isopropyl alcohol, 1,2-butanediol, isobornylcyclohexanol, 2,4-diethyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 2,5-dimethyl-2,5-hexanediol, 2,5-dimethyl-3-hexyne-2,5-diol, 2,3-dimethyl-2,3-butanediol, 1,1,1-tris(hydroxymethyl)ethane, 2-ethyl-2-hydroxymethyl-1,3-propanediol, 2,2′-oxybis(methylene)bis(2-ethyl -1,3-propanediol), 2,2-bis(hydroxymethyl)-1,3-propanediol, 1,2,6-trihydroxyhexane, bis[2,2,2-tris(hydroxymethyl)ethyl]ether, 1-ethynyl-1-cyclohexanol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, erythritol, threitol, guaiacol glycerol ether, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, etc. Examples of glycol ether solvents include diethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, 2-methylpentane-2,4-diol, diethylene glycol monohexyl ether, diethylene glycol dibutyl ether, triethylene glycol monobutyl ether, etc.

[0062] Examples of the surfactant include polyoxyalkylene acetylene glycols, polyoxyalkylene glyceryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene esters, polyoxyalkylene alkylamines, and polyoxyalkylene alkylamides.

[0063] (2) Flux content The content of the flux is preferably 5 to 95% and more preferably 5 to 15% based on the total mass of the solder paste, in which case the effect of suppressing thickening caused by the solder powder is sufficiently exhibited.

[0064] (3) Solder powder The solder powder used in the solder paste according to the present invention is preferably a spherical powder, which improves the fluidity of the solder alloy.

[0065] Furthermore, when the solder alloy is a spherical powder, if it has a size (particle size distribution) corresponding to symbols 1 to 8 in the powder size classification (Table 2) in JIS Z 3284-1:2014, soldering to fine components becomes possible. The size of the particulate solder material is more preferably a size corresponding to symbols 4 to 8, and even more preferably a size corresponding to symbols 5 to 8. The sphericity is preferably 0.90 or more, more preferably 0.95 or more, and most preferably 0.99 or more.

[0066] In the present invention, the diameter and sphericity of the solder alloy, which is a spherical powder, are measured using a CNC image measuring system (Ultra Quick Vision ULTRA QV350-PRO measuring device manufactured by Mitutoyo Corporation) that uses the minimum zone center method (MZC method). In the embodiment, the sphericity indicates the deviation from a true sphere, and is, for example, the arithmetic mean value calculated when the diameter of each of 500 balls is divided by the major axis, and the closer the value is to the upper limit of 1.00, the closer the ball is to a true sphere.

[0067] (4) Manufacturing method of solder paste The solder paste according to the present invention is manufactured by a method generally used in the industry. First, the solder powder can be manufactured by a known method such as a dripping method in which molten solder material is dripped to obtain particles, a spraying method in which centrifugal spraying is performed, or a method in which bulk solder material is crushed. In the dripping method or spraying method, the dripping or spraying is preferably performed in an inert atmosphere or a solvent in order to obtain particles. Then, the above components are heated and mixed to prepare a flux, and the above solder powder is introduced into the flux, stirred, and mixed to manufacture the solder paste.

[0068] 3. Solder balls The solder alloy according to the present invention can be used as a solder ball. When used as a solder ball, the solder alloy according to the present invention can be manufactured into a solder ball by a dropping method, which is a common method in the industry. Also, a solder joint can be manufactured by processing the solder ball by a common method in the industry, such as mounting one solder ball on one electrode coated with flux and joining them. The particle size of the solder ball is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. The upper limit of the particle size of the solder ball is preferably 3000 μm or less, more preferably 1000 μm or less, even more preferably 600 μm or less, and particularly preferably 300 μm or less.

[0069] 4. Solder preform The solder alloy according to the present invention can be used as a preform, which may be in the form of a washer, ring, pellet, disk, ribbon, wire, or the like.

[0070] 5. Solder joints The solder alloy according to the present invention can be used as a joint for joining two or more kinds of various members. There is no limitation on the joining members, and it is useful, for example, as a joint for electronic device members. That is, the solder joint according to the present invention refers to a connection part of electrodes, and can be formed using general soldering conditions.

[0071] 6. Method of forming solder alloy There is no limitation on the method for producing the solder alloy according to the present invention, and the solder alloy can be produced by melting and mixing raw material metals.

[0072] There is no limitation on the method of forming an As-enriched layer in a solder alloy. One example of the method of forming an As-enriched layer is to heat a solder material in an oxidizing atmosphere (air or oxygen atmosphere). The heating temperature is not limited, but may be, for example, 40 to 200°C, or may be 50 to 80°C. The heating time is also not limited, and may be, for example, several minutes to several days, preferably several minutes to several hours. In order to form a sufficient amount of an As-enriched layer, the heating time is preferably 10 minutes or more, more preferably 20 minutes or more. The above-mentioned solder powder, solder ball, and solder preform can also be subjected to this heat treatment to form an As-enriched layer.

[0073] The solder alloy according to the present invention can be manufactured by using a low alpha ray material as its raw material. When such a low alpha ray alloy is used to form solder bumps around a memory, it becomes possible to suppress soft errors. EXAMPLES

[0074] Solder powders having the solder compositions (mass %) of the examples and comparative examples in Tables 1 and 2 and the flux shown in Table 3 were heated and stirred so that the mass ratio of the flux to the solder powder (flux:solder powder) was 11:89, and then cooled to prepare solder pastes, which were then evaluated for 1. temperature cycle characteristics, 2. drop impact test, 3. presence or absence of an As-enriched layer, 4. inhibition of thickening, 5. yellowing, and 6. solder wettability. Comparative Example 2 has the solder alloy composition of Patent Document 1, Comparative Examples 3 and 4 have the solder alloy composition of Patent Document 2, and Comparative Example 5 has the solder alloy composition of Patent Document 3.

[0075] The solder powder used in this example had an average particle size of 21 μm, which corresponds to powder size classification 5 of JIS Z3284-1:2014 (Table 2), and was obtained by heating at 60° C. for 30 minutes in the atmosphere using a drying device. Only in Comparative Examples 44 to 48 was solder powder not subjected to heat treatment used.

[0076] 1. Temperature cycle characteristics 1.) A Sn-plated resistor with dimensions of 3.2 x 1.6 (mm) is mounted on a glass epoxy printed circuit board coated with the solder paste prepared as described above, and is heated and soldered in a reflow furnace.

[0077] 2.) The soldered printed circuit boards were placed in a two-bath automatic testing device with a low temperature condition of -40°C and a high temperature condition of +85°C for 30 minutes each. The printed circuit boards were then removed at the initial, 800th, 1200th, 1600th, and 2000th cycles and shear strength tests were performed on 150 solder joints to check the changes in strength.

[0078] 3.) For the minimum strength in each cycle, if the strength drops significantly (less than 50% from the initial value) or if the strength falls to 10N or less, it is considered to have deteriorated, and the number of cycles at which this occurs is recorded in the table.

[0079] 4.) If the number of cycles exceeds 1600, mark it as "O". If it does not reach 1600, mark it as "X".

[0080] 2. Drop impact test 1.) The flux shown in Table 3 is printed on a CSP having an outer dimension of 12 x 12 (mm) and 196 bumps on the electrodes, and solder balls having a diameter of 0.3 mm and having the compositions shown in Tables 1 and 2 are placed on the CSP.

[0081] 2.) The CSP with the solder balls placed on it is heated in a reflow furnace to form solder bumps on the electrodes.

[0082] 3.) The CSP with solder bumps formed is placed in the center of a 30 x 120 (mm) glass epoxy printed circuit board coated with solder paste, and the CSP is soldered to the printed circuit board by heating in a reflow furnace. The board was left at room temperature for 5 days after soldering.

[0083] 4.) Fix both ends of the printed circuit board with the soldered CSP on the drop jig with a gap of 1 cm between the jig and the jig.

[0084] 5.) The PCB is subjected to an impact by being dropped from a height that applies an acceleration of 1500G to the drop jig. At this time, the PCB, which is fixed to the jig at both ends, vibrates at the center, and the solder joints of the PCB and CSP are subjected to an impact from this vibration. The progress of cracks in the solder joints of the CSP during this drop test is confirmed by checking whether the electrical resistance value increases by 50% from the initial value.

[0085] 6.) The judgement for crack progression is as follows: if the electrical resistance value does not increase by 50% from the initial value after 20 drops, it is marked as "Good", and if it exceeds 50%, it is marked as "Poor".

[0086] 3. Presence or absence of As-enriched layer The presence or absence of an As-enriched layer was evaluated by depth direction analysis using XPS (X-ray Photoelectron Spectroscopy) as follows.

[0087] (Analysis conditions) Analytical equipment: Micro-area X-ray photoelectron spectrometer (AXIS Nova manufactured by Kratos Analytical) Analysis conditions: X-ray source AlKα ray, X-ray gun voltage 15 kV, X-ray gun current value 10 mA, analysis area 700 μm × 300 μm Sputtering conditions: ion species Ar+, acceleration voltage 2 kV, sputtering rate 0.5 nm / min (SiO 2 Conversion) Samples: Three samples were prepared by spreading solder powder having the alloy composition shown in Tables 1 and 2 evenly and tightly on a stage covered with carbon tape. The size of the samples was 5.0 mm x 5.0 mm. This solder powder was used to make the solder paste described above.

[0088] (Evaluation Procedure) An area of ​​700μm×300μm was selected from a sample measuring 5.0mm×5.0mm, and XPS analysis was performed on each of the Sn, O, and As atoms while performing ion sputtering to obtain an XPS analysis chart. One area was selected for each sample, and the analysis was performed once for each of the three samples, for a total of three times.

[0089] Examples of charts obtained by XPS analysis are shown in Figures 1 to 3. Figures 1 to 3 show the same sample with the detection intensity (cps) scale changed on the vertical axis, and the SiO 2 In the XPS analysis chart, the vertical axis is the detection intensity (cps), and the horizontal axis is the sputtering time (min) or the time from the sputtering time to the SiO 2 SiO calculated using the sputter etching rate of the standard sample 2 In Figures 1 to 3, the horizontal axis of the XPS analysis chart is selected from the sputtering time to the SiO 2 SiO calculated using the sputter etching rate of the standard sample 2 The converted depth was expressed as nm.

[0090] In the XPS analysis chart of each sample, the SiO 2 The conversion depth was defined as Do·max (nm) (see Fig. 2). The first SiO 2 The converted depth was defined as D1 (nm).

[0091] Next, in the XPS analysis chart of each sample, the area from the outermost surface to a depth of 2 × D1 (SiO 2 The integral value (S1) of the As detection intensity in the region from 0 to 2×D1 (nm) converted to a depth of 0 to 2×D1 (nm) and the region from 2×D1 to a depth of 2×D1 (SiO 2 The integral value (S2) of the As detection intensity in the region of 2×D1 to 4×D1 (nm) converted to a depth of 100 nm (see FIG. 3) was calculated and compared.

[0092] And the evaluation was carried out based on the following criteria. -S1>S2 in all three measurements : As-enriched layer is formed (○) -S1>S2 in 2 or less of the 3 measurements : No As-enriched layer is formed (×) 4. Suppression of thickening The viscosity of the solder paste used in "1. Temperature cycle characteristics" above was measured for 12 hours using a rotational viscometer (PCU-205, manufactured by Malcom Co., Ltd.) at a rotation speed of 10 rpm and a measurement temperature of 25° C. according to the method described in "4.2 Viscosity characteristic test" of JIS Z 3284-3:2014. The initial viscosity (viscosity after 30 minutes of stirring) was then compared with the viscosity after 12 hours, and the thickening suppression effect was evaluated based on the following criteria.

[0093] Viscosity after 12 hours ≦ Initial viscosity × 1.2: Viscosity increase over time is small and good (○) Viscosity after 12 hours > initial viscosity x 1.2: Viscosity increase over time is large, poor (×) 5. Yellowing prevention Solder balls (0.3 mm diameter) having the alloy composition shown in Tables 1 and 2 were heat-treated in the atmosphere at 60°C for 30 minutes using a drying device, and then heated in an air atmosphere in a thermostatic chamber at 200°C for 2 hours. The yellowness b* in the L*a*b* color system was measured for the solder balls before and after heating, and the increase (Δb*) was calculated by subtracting the b* before heating from the b* after heating.

[0094] The yellowness index b* was calculated from the color values ​​(L*, a*, b*) by measuring the spectral transmittance using a CM-3500d2600d spectrophotometer (Konica Minolta) under a D65 light source and a 10-degree visual field in accordance with JIS Z 8722:2009 "Method of measuring color - Reflection and transmission object color." The color values ​​(L*, a*, b*) are based on the JIS Z 8781-4:2013 standard.

[0095] Δb* value is 50% or less of Δb* (standard): ◎ (very good) Δb* value is more than 50% and less than 70% of Δb* (standard): ○ (good) Δb* value is greater than 70% of Δb* (standard): × (not acceptable) 6. Solder wettability Flux WF-6400 (manufactured by Senju Metal Industry Co., Ltd.) was printed to a thickness of 0.115 mm on a bare copper electrode pad (opening diameter of electrode on substrate (solder resist opening): 0.24 mm), and the solder ball used in "5. Suppression of yellowing" was mounted on top of it. The electrode pad with the solder ball mounted was heated from 25°C at a heating rate of 1°C / sec with N 2 The temperature was raised to 260°C in an ambient atmosphere and reflow was performed. After reflow, the electrode pads with the solder balls mounted were immersed in distilled water and ultrasonically cleaned for 1 minute. The number of bumps that were not soldered and disappeared during the cleaning process (number of missing bumps) was counted and evaluated based on the following criteria.

[0096] 0 missing bumps out of 100 bumps: ◎ (very good) 1 to 5 missing bumps out of 100 bumps: ○ (good) 6 or more missing bumps out of 100 bumps: × (not acceptable) 7. Overall rating If all the above tests were marked as "good" or "excellent", then the rating was marked as "good". If any test was marked as "bad", then the rating was marked as "bad". The results are shown in Tables 1 and 2.

[0097] [Table 1]

[0098] [Table 2]

[0099] [Table 3]

[0100] As shown in Tables 1 and 2, in the examples, all of the samples had excellent temperature cycle characteristics and drop impact resistance, had an As-rich layer, suppressed thickening and yellowing of the paste, and were excellent in wettability. On the other hand, in Comparative Examples 1 to 43, none of the alloy compositions satisfied at least one of the requirements of the present invention, and therefore at least one of the evaluation items was poor. In addition, since Comparative Examples 1 to 11 did not contain As, the presence or absence of an As-rich layer was not evaluated. In addition, since Comparative Examples 44 to 48 were not subjected to heat treatment, surface concentration of As could not be confirmed, thickening of the solder paste was not suppressed, and the solder alloy turned yellow.

Claims

1. The solder alloy contains, by mass%, 0.2 to 1.2% Ag, 0.6 to 0.9% Cu, 1.2 to 3.0% Bi, 0.01 to 2.0% In, 0.02 to 1.0% Sb, 0.0040 to 0.025% As, and the balance being Sn. The solder alloy has an As-enriched layer, the presence of which is confirmed by the following criteria. The As-enriched layer is a layer of SiO 2 The As-enriched layer is a region up to a depth of 2×D1 (nm) in terms of the converted depth. 2 A solder alloy having a converted thickness of 0.5 to 8.0 nm. (Judgment criteria) An arbitrary area of ​​700 μm×300 μm is selected from a sample measuring 5.0 mm×5.0 mm, and an XPS analysis is performed in combination with ion sputtering. One area is selected for each sample, and three analyses are performed once for each of the three samples, for a total of three analyses. If S1>S2 in all three analyses, it is determined that an As-enriched layer has been formed. Where: S1: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 0 to 2×D1 (nm) converted depth S2: In the XPS analysis chart, SiO 2 The integral value of the As detection intensity in the region of 2×D1 to 4×D1 (nm) converted depth D1: SiO where the detection intensity of O atoms was maximum in the XPS analysis chart 2 The first SiO where the detection intensity of O atoms becomes half the maximum detection intensity (intensity at Do max) in a portion deeper than the conversion depth (Do max (nm)). 2 The equivalent depth (nm).

2. A solder paste comprising a solder powder made of the solder alloy according to claim 1 and a flux.

3. A solder ball made of the solder alloy according to claim 1.

4. A solder preform comprising the solder alloy according to claim 1.

5. A solder joint formed from the solder alloy of claim 1.

Citation Information

Patent Citations

  • Solder alloys, solder pastes, solder balls, solder preforms, and solder joints

    JP6810374B1

  • Soldering material and electric / electronic device using the same

    WO2000018536A1

  • Lead-free solder alloy

    WO2012128356A1

  • Solder material, solder paste, and solder joint

    WO2019103025A1

  • Transformer holding relay integral remote control relay operated by pushbutton switch

    JP1983007733A